Tahapan dan Langkah-Langkah Penerapan Mixed Method Research (MMR) dalam Penelitian Pendidikan - Khabibullah, Muttaqin; Alimin; Sholahuddin, Gus Malik Imam (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
Many academics believe that using questionnaires and interviews simultaneously, or combining statistical analysis and narrative interpretation, can be categorized as mixed method research (MMR). This view is not entirely correct, but it is not entirely wrong either. MMR involves integrating quantitative and qualitative methods in a study, including all related components. However, not all simultaneous uses of quantitative and qualitative data collection and analysis techniques can be considered MMR, as several key factors, such as timing, weighting, and research objectives, must be taken into account. This article aims to elaborate on various MMR models and their implementation steps, using a literature review method. The study identifies six MMR models: Sequential Explanatory, Sequential Exploratory, Concurrent Triangulation, Concurrent Embedded, Sequential Transformative, and Concurrent Transformative. However, the last two models are not discussed in detail due to their lower popularity. The Sequential Explanatory model integrates quantitative and qualitative methods sequentially, with greater emphasis on quantitative methods to provide additional information. Similarly, the Sequential Exploratory model is conducted sequentially but places more weight on qualitative data to connect findings. The Concurrent Triangulation model integrates both methods simultaneously, with equal weighting to compare data, while the Concurrent Embedded model combines the methods simultaneously but prioritizes one as the primary method and the other as the secondary method, aiming to compare data. Our findings provide practical guidelines for researchers in implementing each MMR model, particularly by highlighting aspects that are often overlooked in previous literature. These guidelines are expected to help researchers select and apply models that align with their research needs.